If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 60 = x + -6 Reorder the terms: 60 + 7x = x + -6 Reorder the terms: 60 + 7x = -6 + x Solving 60 + 7x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 60 + 7x + -1x = -6 + x + -1x Combine like terms: 7x + -1x = 6x 60 + 6x = -6 + x + -1x Combine like terms: x + -1x = 0 60 + 6x = -6 + 0 60 + 6x = -6 Add '-60' to each side of the equation. 60 + -60 + 6x = -6 + -60 Combine like terms: 60 + -60 = 0 0 + 6x = -6 + -60 6x = -6 + -60 Combine like terms: -6 + -60 = -66 6x = -66 Divide each side by '6'. x = -11 Simplifying x = -11
| 45=-5(k+4) | | 2/5x-=1/5x-12 | | 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 | | -3.5b-1.75c= | | 4X+20=25-x | | x-2(-2x+20)=20 | | c/2=-14 | | X^2+27x-18=0 | | d=7.25t | | 1.1x=94000 | | -4(2t+5)=-60 | | 24x+7x=19 | | =11x+5y-30z | | 2^3x=1/8 | | -10(s+4)=-78 | | 2.5=0.6*[19.6(1-.61*x)]^(1/2)*2*x | | 324x^4-4y^4= |